Strategic planning paper for Davao Oriental Electric Cooperative - Delizo, Estella Marie A. (School of Management, University of the Philippines Mindanao, 2011)
Rural electrification is a pro-poor flagship program of the Government of the Philippines which aims to improve the quality of life in rural areas through the provision of adequate, affordable and reliable energy services in a sustainable manner. This paper deals with the formulation of a strategic plan for the Davao Oriental Electric Cooperative (DORECO) which was organized and registered with the National Electrification Administration (NEA) on December 30, 1977 as non-stock, non-profit, non-political and member-owned electric by virtue of Presidential Decree No. 269 with its main office located at Mati, Davao Oriental. This is designed to formulate a strategic plan for DORECO using the company's data from 2006-2010. The company's internal and external environments, and its corporate mission, vision and objectives are thoroughly analyzed to come up with the strategic plan to meet the demands of the changing environment. After the analysis, it was then revealed that the following are the strengths, weaknesses, opportunities and threats of DORECO: Strengths; the company has strong corporate values, their organizational structure encompasses both vertical and horizontal levels of management, the management gained the trust and confidence of the employees and member-consumers, the organization is strong and united, employees are efficient despite the lack of manpower. WEAKNESSES; increasing system loss, weak consumer education, substandard service drop wires, decreased collection efficiency. OPPORTUNITIES; Davao Oriental is a captive market, increasing demand for electricity is brought about by recent developments in infrastructure, health and agriculture, possible avenues in power can be seen in the natural resources of Davao Oriental, assistance from the government is readily accessible. THREATS; limited room for expansion and private acquisition of investments, the Rural Electric Cooperative model was not without its risks, the susceptibility brought by political influence in the company could also affect the performance of ECs, aside from the acquisition and expansion restriction, ERC also have strict requirements for innovation. Having identified the strengths, weaknesses, opportunities, and threats of DORECO, it is by strengthening member empowerment through marketing and product development were seen as the best possible strategies for the company?s current status.